Community assembly after long-term fragmentation: a case study of tropical rainforest in Xishuangbanna, south-west China. (2nd January 2016) - Liu, Yingying
Abstract : Background : Tropical rainforests represent the most species-rich and at the same time the most fragmented terrestrial biome on Earth. Fragmentation of tropical rainforests is having wide-ranging consequences for the maintenance of local species diversity and community assembly patterns. Aims : To examine floristic changes and changes in community phylogenetic structure in the forest fragment over the past five decades. Methods : A new taxonomic diversity algorithm (within-family diversity) was developed to assess floristic changes in the forest fragment. Community phylogenetic structure was then compared before and after fragmentation. Results : Taxonomic diversity changed greatly among families, with changes occurring randomly across the phylogeny. The forest fragment had higher phylogenetic diversity, higher mean pair-wise phylogenetic distance, but lower mean nearest-neighbour distance. The community phylogenetic structure has changed significantly from clustering to dispersion. Conclusions : High species turnover occurred in the forest fragment. While shade-tolerant species have been lost, and ruderal and alien species have been added, overall phylogenetic diversity has increased with species being more phylogenetically distant. Competitive exclusion, which was related to the relatively drier conditions in the forest after fragmentation, led the plant community phylogenetic structure to be more dispersed.